Transformation and Enhancement of Climate Change Policy Indicators (2022)
ABSTRACT: Chapter 6 underlines the need for accurate metrics to support climate policy implementation and remarks on how existing quantitative metrics can be adapted to integrate multiple indicators. This chapter includes a concrete example of how landscape shock may trigger new policies and how metrics might help monitor regime destabilisation and niche development.